COLLABORATIVE PRACTISE AS THE INTERSECTION BETWEEN DIGITAL LEARNING AGILITY AND TEACHERS’ PROFESSIONAL DEVELOPMENT - Mas Nida Md Khambari; Nur Dania Mohd Rosli; Kamilah Abdullah; Su Luan Wong; Noor Syamilah Zakaria; Priscilla Moses; Nur Aira Abdrahim, (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
The volatile, uncertain, complex, and ambiguous (VUCA) world and IR4.0 developments forces drastic changes to sustain and provide quality education. When schools were shut down abruptly due to COVID-19, teachers were forced into emergency remote teaching, mostly by utilising technologies but with little to no specific structure. However, teachers who are digitally agile could maneuver the unprecedented situation. This study therefore explores the role of collaborative practise as the intersection between digital learning agility and teachers’ professional. A qualitative case study approach was employed, involving semi-structured interviews with 20 primary and secondary school teachers, and five school administrators over the course of two months. Data were analysed using thematic analysis to identify key patterns and insights related to collaborative practices as a component of digital learning agility and teachers’ professional development. Three main themes that emerged from the analysis were (i) acquisition of new skills and knowledge, (ii) peer support, mentorship and resource sharing, and (iii) innovation, reflection and institutional growth. This highlights the necessity for organised and supportive collaborative settings that enable educators to explore and implement digital technologies, so that it could enhance both the personal and institutional efficacy. The challenges posed by the pandemic, the exponential use of ICT during the time and active collaboration among teachers has contributed to their professional development.